Interpretasi pengukuran risiko antar lembaga ‎pembiayaan syariah: Studi kasus pada BMT X di Kota ‎Tasikmalaya dengan lembaga pembiayaan syariah di ‎Kota Makassar - Sufia, Ilma; Shalsabila, Izzatunnisa' Habiba; Carolina, Nadia Intan (Maliki Interdisciplinary Journal, 2023)
The purpose of this research is to find out and interpret how to risk measurement between Islamic financing institutions, namely at one of the BMTs in Tasikmalaya and one of the Islamic Financing Institutions in Makassar. The approach of this study qualitative data on study of literature review. The type of data used is secondary data from national publication data through the Garuda website (garuda.kemdikbud.go.id). Data collection starts since May 2022 by using the search feature on Garuda with the keyword "Risk Measurement". The conclusion of this study is a found of differences between the two ways of risk measurement in Islamic financing institutions that is Islamic maqashid measurements produces more detailed measurements compared to conventional methods.